Exploring Punjabi Folk Music ‘Jugni’ Through the Prism of Grice’s Cooperative Principle and Conversational Implicature - Noor, Faseeha; Riaz, Marryam (Pakistan Journal of Humanities and Social Sciences, 2024)
The selected song ‘Jugni’ is a renowned Punjabi folk music with various versions that have evolved across sub-continent over several centuries. The prior studies focused on interpretation of interviews, advertisements, cartoons, and daily conversations from the perspective of discourse analysis. However, the current research aims to highlight and fill in the prevalent gap of overlooking folk music by analyzing lyrics of Jugni and identifying its multi-faceted approach. By utilizing qualitative method through focus group observation and content analysis, the study contemplates on Grice (1975) Conversational Implicatures and Cooperative Principle. The research findings concluded that Jugni adheres to four Gricean Maxims. However, its implicature analysis adds on understanding of the embedded narratives of Religion, Sufism, Philosophy, Feminism, and Punjabi Culture. It signifies the need of attention on folk music and literature in the domain of discourse analysis.